PERANCANGAN APLIKASI SISTEM INFORMASI LAPORAN TES HIV MENGGUNAKAN VISUAL BASIC.NET DI RSUD AL-IHSAN BANDUNG - Muhamad Maulana Maulana (POLITEKNIK PIKSI GANESHA, 2022)
Al-Ihsan Regional General Hospital is a health facility in West Java that seeks to control HIV (Human Immunodeficiency Virus) in the form of voluntary test counseling for people who feel infected, and provide recommendations to patients with a history of TB, heart disease, cancer, hemodialysis, pregnant women to do an HIV test. This study aims to provide an overview of an information system application that can make it easier to collect identity data and history of patient test results directly, without the need to manually collect such as by looking for patient data first at SIMRS then looking for test results history in VANSLAB View then in input into Microsoft Excel. The design method uses the Waterfall model, the stages are requirement, design, implementation, testing, maintenance. This application can generate patient data as well as test history directly without having to collect it manually. With this application, it can provide convenience for officers who will send reports.